Childhood intussusception: Impact of delay in presentation in a developing country - Olakayode Olaolu Ogundoyin; Dare Isaac Olulana; Taiwo Akeem Lawal (Wolters Kluwer Medknow Publications, 2016)
Background: The classical cases of intussusception are readily diagnosed clinically, and despite recent improvements in radiological techniques, the diagnosis of intussusception and success in its nonoperative reduction has been suboptimal, thus making operative management a veritable backup. This study examined the impact of delays in presentation on the rate of bowel resection, length of hospital stay, and appraised the outcome of operative treatment. Patients and Methods: This was a retrospective study of consecutive children admitted and treated surgically for intussusception between January 2002 and December 2011 at the University College Hospital, Ibadan, Nigeria. Results: The mean age at presentation was 13.4 months with a male: female ratio of 1.8:1. Fourteen patients (25.5%) presented within the first 24 h of onset of symptoms with majority (36.4%) presenting between 2 and 3 days of onset of symptoms. The primary surgical intervention was performed on 47 patients (85.5%), and the secondary operative intervention was performed on eight patients (14.5%) who had failed initial nonoperative management of intussusception. Manual reduction of intussusception was performed on 27 patients (49.1%), 26 patients had resection of gangrenous bowel with end-to-end anastomosis while two patients (3.6%) had spontaneous reduction of intussusception which was discovered at laparotomy. The mean duration of hospital stay was 12.1 days (range 3-60 days). The overall mortality was 5.5% (three patients), and three patients (5.5%) had recurrence of intussusception. Conclusion: Although mortality is reducing, a high rate of bowel resection is a consequence of delayed presentation and effort should be made to make an early diagnosis of intussusception and make prompt referral to improve outcome.